Financial Derivatives in Corporate Tax Aggressiveness - Bendi Devi; Subagio Efendi (The Indonesian Journal of Accounting Research, 2018)
Abstract: The purpose of this study is to investigate the utilization of derivative financial instruments in tax aggressiveness activities. The study is conducted by using the fair value of the financial assets and liabilities derived in total and divided on hedge design to identify the derivatives used for tax evasion. The results of the analysis show that cash effective tax rate (Cash ETR) is negatively associated with the fair value of hedging derivative assets. This indicates that the company reduced tax payments by delaying the realization of derivative profits designated hedging. Furthermore, Cash ETR is found to be negatively (positive) correlated with the fair value of non-hedging derivative assets (liabilities). This indicates that the company delayed the realization of the profit while accelerating the realization of the loss of non-hedging derivatives to reduce the tax paid. Then, GAAP ETR is positively correlated with the fair value of the non-hedging derivative liability, indicating that there is a reduction of tax expense through an accelerated realization of non-hedging derivative loss so that it can be said that the company does earnings management activity through minimization tax expense using derivative financial instruments. This study contributes to the Indonesian tax authorities by providing policy recommendations related to financial derivative transactions because up to the time of this research, Indonesia does not have tax rules that specifically regulate taxation on financial derivatives transactions.Abstrak: Tujuan penelitian ini adalah untuk menginvestigasi pemanfaatan instrumen keuangan derivatif dalam aktivitas agresivitas pajak. Penelitian dilakukan dengan menggunakan nilai wajar aset dan liabilitas derivatif keuangan secara total dan terbagi berdasarkan desain lindung nilai untuk mengidentifikasi derivatif yang digunakan untuk penghindaran pajak. Hasil analisis menunjukkan cash effective tax rate (Cash ETR) berasosiasi negatif signifikan dengan nilai wajar aset derivatif lindung nilai. Hal ini menunjukkan bahwa perusahaan mengurangi pembayaran pajak dengan menunda realisasi laba derivatif yang didesain lindung nilai. Selanjutnya, Cash ETR ditemukan berkorelasi negatif (positif) signifikan dengan nilai wajar aset (liabilitas) derivatif non-lindung nilai. Hal ini mengindikasikan bahwa perusahaan menunda realisasi laba sekaligus mempercepat realisasi rugi derivatif non-lindung nilai untuk mengurangi pajak yang dibayar. Kemudian, GAAP effective tax rate  (GAAP ETR) berkorelasi positif signifikan dengan nilai wajar liabilitas derivatif non-lindung nilai, mengindikasikan bahwa terjadi pengurangan beban pajak melalui percepatan realisasi rugi derivatif non-lindung nilai sehingga dapat dikatakan juga bahwa perusahaan melakukan aktivitas manajemen laba melalui minimalisasi beban pajak menggunakan instrumen keuangan derivatif. Penelitian ini berkontribusi pada otoritas pajak Indonesia dengan memberikan rekomendasi kebijakan terkait transaksi derivatif keuangan karena hingga sampai saat penelitian ini dilakukan Indonesia belum memiliki aturan pajak yang secara khusus mengatur pemajakan atas  transaksi derivatif keuangan.